Examining the influence of team work factors on team performance for software Development team in telecommunication industry in Iraq: A structural equation modeling - Ahmed, Vian Abdulmajeed (2016)
Software development requires team work. Research has shown that a number of projects have been failed in software industry due to cost and schedule overruns. One of the major reasons for the project failure is poor performance of software team. There are a number of factors that would affect team performance, such as coordination of expertise, communication, mutual support and value diversity. The main objective of this study is to identify team work factors that have significant effect on the performance of the software development team. This study used questionnaire to investigate the impacts of the above factors on team performance. The respondents consist of one hundred and six software developers from telecommunication industry in Iraq and Kurdistan Region Government (KRG). The analysis of the data was conducted using Structural Equation Modeling (SEM) to examine relationship significance of the identified factors on software development team performance. The result of the study was helpful for analyzing the relationship between teamwork factors and team performance. The result shows that communication, mutual support and coordination of expertise have significant influence on the performance of software development team. The findings of this study provide researchers and organizations with new insights into the determinants of the factors that affected performance of software development teams, and can help the managers to build an effective team which lead to increase organization performance.